Financial Intermediation, Market Liquidity, and Firm Value: A Panel Analysis of ASEAN Banks - Mahendra, Putra; Amelia, Rizky (Universitas Sains dan Teknologi Komputer, 2026)
ASEAN economic integration aims to build an efficient banking sector that channels funds and maintains market liquidity, thereby increasing firms’ values. The performance of financial intermediation and banks' liquidity in the region has been unstable since the pandemic; nevertheless, this has not benefited firms, as it has driven their values down. The present research seeks to measure the impact of financial intermediation and market liquidity on banks' value in ASEAN and to explore differences across countries. By relying on a panel dataset derived from 80 banks situated in five different ASEAN countries during the years 2015–2023 and applying the Dynamic Panel Data method focusing on the Generalized Method of Moments (GMM), the study concludes that, in general, both financial intermediation and market liquidity significantly and positively impact the firm value, with the former being the stronger factor. Profitability fortifies this connection, while leverage seems to have no effect. The analysis of countries shows that the role of intermediation is largest in Indonesia and Vietnam, while Singapore and Malaysia are more affected by liquidity. The main contribution of this work is the simultaneous use of two important financial factors in a single dynamic cross-country model, which allows us to better understand how intermediation efficiency and liquidity together increase firm value. These results highlight the need for market integration policies and for improving intermediation efficiency to make the ASEAN banking sector more competitive.